Electronic Contract and its Effects According to the Sudanese Electronic Transactions law for the Year (2007) A Comparative Study - Mohammed Alnour, Joda Ibrahim (Gezira Journal of Economic and Social Sciences, 2019)
The most important thing that distinguishes the electronic contract from the traditional contract is the means through which it passes through it through an electronic environment that uses modern means of communication, especially the internet. The study aimed at: To learn about the concept of e-contract and its advantages. Highlighting the languages ​​of affirmation and electronic acceptance and its characteristics. The study followed the descriptive historical descriptive method. The study found many results, including: Electronic contracts are usually concluded online, a network open to users around the world, especially in the case of mutual exchange and acceptance through the site, it creates a problem on how to determine the personality of the parties to the contractual process for the purpose of providing In this case, the owner of the site that is exchanging the offer and acceptance of the other must identify the persons who use it, if not the obligor or the owner of the site itself, Sudan is one of the first Arab countries that has an electronic transactions law is the law of (2007). Only Jordan, the Emirate of Dubai, Bahrain, Tunisia and Lebanon. preceded this. In addition, the method of expression in contracts for acceptance of online contracts is consistent with the method of contracting. An icon or by entering private information, and we find no value for silence as an expression of acceptance in electronic contracts. The study recommended the following: We propose to amend some articles of the Sudanese civil law to be in a way that shows (concluding contracts by means of modern communication) to accommodate all the new developments in communications, and the means of contracting modern, such as the Internet. As well as the creation of special websites on the net providing advice and guidance to provide protection to the less experienced party in the electronic contract.        أهم ما يميز العقد الالكتروني عن العقد التقليدي هو تلك الوسيلة التي يمر عن طريقها، بحيث يتم من خلال بيئة الكترونية تستخدم فيها وسائل الاتصال الحديثة وعلى رأسها شبكة الانترنت. هدفت الدراسة إلى التعرف على مفهوم العقد الإلكتروني ومميزاته. وإبراز لغات الإيجاب والقبول الإلكتروني وخصائصه. اتبعت الدراسة المنهج الوصفي التاريخي الاستقرائي. توصلت الدراسة إلى العديد من النتائج من بينها: إن العقود الإلكترونية مبرمة عادة عبر الإنترنت، وهي شبكة مفتوحة أمام المستخدمين في جميع أنحاء العالم خاصة في حالة تبادل الإيجاب والقبول من خلال الموقع، فإن ذلك يخلق مشكلة تتعلق بكيفية تحديد شخصية طرفي العملية التعاقدية وذلك لغرض توفير الأمان القانوني لها، ففي هذه الحالة يجب على صاحب الموقع الذي يجري تبادل الإيجاب والقبول غيره، أن يقوم بتحديد الأشخاص الذين يستخدمونه، هذا إن لم يكن الموجب أو القابل صاحب الموقع نفسه، السودان من أوائل الدول العربية التي لديها قانون للمعاملات الإلكترونية وهو قانون المعاملات الإلكترونية لسنة (2007م) ولم يسبقه في ذلك إلا الأردن، إمارة دبي، البحرين، تونس، لبنان، بالإضافة إلى أن أسلوب التعبير في العقود عن القبول في العقود التي تتم عبر الإنترنت يكون متماشياً مع طريقة التعاقد فقد يكون عن طريق النقر عدة مرات على إيقونة ما أو عن طريق إدخال معلومات خاصة، ولا نجد قيمة للسكوت باعتباره تعبيراً عن القبول في العقود الإلكترونية. أوصت الدراسة بالآتي: نقترح تعديل بعض مواد القانون المدني السوداني لتكون بشكل يوضح (إبرام العقود بوسائل الاتصال الحديثة) لتستوعب كل ما يستجد على صعيد الإيصالات، ووسائل التعاقد الحديثة كالإنترنت. كذلك استحداث مواقع إلكترونية خاصة على الشبكة تقدم النصائح والإرشادات لتوفير الحماية للطرف الأقل خبرة في العقد الإلكتروني.